THE EFFECT OF PRICE AND PRODUCT COMPLETENESS ON CONSUMER PURCHASE DECISIONS AT INDOMARET DIPONEGORO TAKALAR - Muchran Muchriady; Muchran Murniady; Mursalim Mursalim (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims 1) to determine the effect of price on purchasing decisions at Indomaret Diponegoro Takalar. 2) to determine the effect of product completeness on purchasing decisions custumers at Indomaret Diponegoro Takalar. The type of research used in this research is quantitative with a sample of 96 respondents. Data collection techniques using a questionnaire technique. The data analysis technique used multiple linear regression test. The results showed that the price and product completeness had a positive and significant effect on purchasing decisions costumers at Indomaret Diponegoro Takalar.